THE ROLE OF THE FAMILY IN THE DIAGNOSIS OF ADHD - Ribeiro Rubim Fernandes, Ivete; Rubim Fernandes, Leticia; Ribeiro Farias e Farias, Madalena (Revista Gênero e Interdisciplinaridade, 2023)
This article deals with the role of the family in the proper diagnosis of ADHD, from the process involved in the theme, our general objective is: To analyze and discuss the role of the family in the learning process of the person with ADHD, to discuss the educational needs experienced during their teaching-learning process. Moving on to working on the specific objectives: Identifying the family’s role in the diagnosis and necessary interventions; This study adopts the methodology of literature and documentary review on the subject, whose data are in the qualitative perspective; Arguing and confronting the data, supported by the experiences of authors who base the Attention Deficit/Hyperactivity Disorder (ADHD) as a neurobiological disorder that has the characteristic of inattention, restlessness, impulsivity and hyperactivity. Since the subjects are both children and adults, it is independent of gender, age and academic background. Symptoms appear mainly in situations that require greater attention and the performance of repetitive tasks. This article is justified by the importance of the family for the development of potentialities and improvement of the personal and social quality of life of the person diagnosed with ADHD, starting to understand its impacts and understand it.